2021
DOI: 10.3390/min11010050
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Studies on Flotation Performance of Saturated Fatty Acids and Unsaturated Fatty Acids Separated from Hogwash Oil

Abstract: Low flotation recovery, high pulp temperature, and large dosage of reagents are the typical disadvantages when using mixed fatty acids (MFA) prepared from hogwash oil for flotation directly. To determine the type of fatty acid that yields poor flotation performance, flotation performance and adsorption characteristics of saturated fatty acids (SFA) and unsaturated fatty acids (UFA) separated from the MFA were studied in our work. GC-MS, FT-IR, iodine value detection and melting point measurement showed that UF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…For the hydrocarbon oil–fatty acid mixed collector, it can be found that there are both saturated and unsaturated fatty acids in the choice of fatty acids. In some mineral flotation, researchers have found that mixed fatty acids with a higher proportion of unsaturated fatty acids can enhance flotation. , However, research on the mechanism by which fatty acid saturation affects LRC flotation is still limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the hydrocarbon oil–fatty acid mixed collector, it can be found that there are both saturated and unsaturated fatty acids in the choice of fatty acids. In some mineral flotation, researchers have found that mixed fatty acids with a higher proportion of unsaturated fatty acids can enhance flotation. , However, research on the mechanism by which fatty acid saturation affects LRC flotation is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…In some mineral flotation, researchers have found that mixed fatty acids with a higher proportion of unsaturated fatty acids can enhance flotation. 13 , 14 However, research on the mechanism by which fatty acid saturation affects LRC flotation is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the oxygen groups contained in waste oil contribute to the hydrophobization of carbon, and confirmed the excellent separation performance of fly ash and unburned carbon. Guo et al (2021) conducted a study on the flotation performance and adsorption properties of saturated and unsaturated fatty acids isolated from hogwash oil to determine which fatty acids have negative effect on the flotation performance. They performed quartz flotation to compare that unsaturated fatty acid shows the excellent adsorption properties on the surface of quartz.…”
Section: Introductionmentioning
confidence: 99%